Understanding gender-based sexual violence against women and girls: breaking the culture of silence - Sciarrino, Nicole A. (Lexington Books, 2023)
"Gender-based sexual violence (GBSV) against women and girls has been woven into societies around the world, resulting in a widespread public health problem. This book explores the impact of GBSV against women and girls across the lifespan and in different cultures and countries to raise awareness to this problem and help decrease stigma"--